2008
DOI: 10.1016/j.jesp.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Imagining intergroup contact promotes projection to outgroups

Abstract: Three studies investigated the conditions under which imagining intergroup contact would lead to greater projection of positive traits to outgroups. In Experiment 1 (Mexico) imagined contact predicted greater self-outgroup positive trait overlap for majority but not minority ethnic groups. In Experiment 2 (UK) imagined contact led to greater projection of positive traits to the outgroup for lower compared to higher identifiers. In Experiment 3 (UK) imagined contact led to greater projection of positive traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
249
5
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(271 citation statements)
references
References 93 publications
15
249
5
2
Order By: Relevance
“…Contrary to Stathi and Crisp (2008) who found projection mainly on positive traits, we found that if projection occurs more in cooperation than in competition, this is the case for both positive and negative traits.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to Stathi and Crisp (2008) who found projection mainly on positive traits, we found that if projection occurs more in cooperation than in competition, this is the case for both positive and negative traits.…”
Section: Discussioncontrasting
confidence: 99%
“…Cooperation, Competition and Interpersonal Projection 17 outgroup projection had already shown that perceived intergroup interdependence moderates projection (Riketta & Sacramento, 2008) and that positive ingroup-outgroup contacts increase outgroup projection (Stathi & Crisp, 2008). The current experiments extend this work to the interpersonal level.…”
Section: Accepted Manuscriptsupporting
confidence: 68%
See 1 more Smart Citation
“…Despite these encouraging findings, the imagined contact field still faces challenges: some have been unable to replicate the imagined contact effects [48][49][50][51]; others have found limited effects of imagined contact among minority group members [52]; it is not clear how long the effects last for adults or how imagined contact is most effectively combined with other forms of contact; and, as with other contact interventions [23*], effect sizes are typically small.…”
Section: Imagined Contactmentioning
confidence: 99%
“…Heterosexuals who imagined talking to a homosexual on a train subsequently evaluated homosexuals in general more positively and stereotyped them less than participants who imagined a neutral scene. Research has also shown that positive imagined contact leads to projecting positive traits to the target outgroup (Stathi, Crisp, 2008). Nonetheless, this technique has certain limitations.…”
Section: Imagined Intergroup Contact Hypothesismentioning
confidence: 99%